PALEOCLIMATIC INFORMATION RECORDED IN FLUID INCLUSIONS IN HALITE FROM CHAKA SALT LAKE, QINGHAI PROVINCE - Ge C.D.; Wang T.G.; Meng F.W.; Liu J.Q.; Liu X.Q. (My University, 2007)
Salt lake from inland arid area is one of effective carriers for research of the ancient climate changes, and fluid inclusions in halite is a powerful mean to reveal the paleoclimate. Chaka Salt Lake in Qinghai Province is a comprehensive salt mine formed in Later Pleistocene, which is mainly composed of halite with coexisting solid and liquid. Study on the homogenization temperature of fluid inclusions in salt core samples from Chaka Salt Lake, indicates that the water temperature of salt lake is gradually elevated from 20°C-30°C in early stage to about 40°C in late stage since 5ka. These results suggested gradually rising for ancient climatic temperature in Chaka area, which is consistent with general trend of the global warming. It is indicated that the homogenization temperatures obtained from primary single phase liquid fluid inclusions in halite (salt) by cooling-heating methods is an efficient new mean to acquire water temperature data of salt lake and thus to reconstruct the paleoclimatie changes. Fluid inclusion method will definitely have further wide applications in salt lake investigating field.
Keywords: CHAKA SALT LAKE; HALITE; HOMOGENIZATION TEMPERATURE; PALEOCLIMATIC INFORMATION; PURE LIQUID PHASE INCLUSION; QINGHAI PROVINCE; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен